Enhancing Pronunciation through Imitation: A Pilot Study among Undergraduates of Technical University - SARALA THULASI PALPANADAN; Safra Liyana Sukiman; Javarina Dee Ann Jack; Rodrick Anak Rantai; Nur Syahirah Asyiqin Buserah; Nila Anak Moris; Sarinah Alim (Development in Language Studies, 2021)
A good communication ability in English is important for everyone including students, employees and even employers. There are many aspects of communication such as pronunciation that require attention in order to improve the overall ability in communication. One of the ways to improve pronunciation is by using imitation technique. Thus, this study was conducted to explore the challenges faced by the university students in pronouncing English words well. A total of 51 respondents from a technical university in Malaysia participated in this pilot study. A questionnaire was distributed to the respondents via Google Form. The data was collected and analysed thoroughly to investigate the pronunciation challenges among the respondents and the effectiveness of imitation technique. It was found that the majority of the respondents feared being belittled due to wrong pronunciation that they chose not to communicate much. The study also found that most of the respondents were in favour of the imitation technique to improve their pronunciation skills. Thus, the study is hoped to enhance the pronunciation ability among the university students in order to improve their overall communication skills.